LEGAL ASSUMPTION AS THE BASIS FOR REMOVAL OF BURDEN OF PROOF - Golts, Edgars (Administrative and Criminal Justice, 2019)
This work is part of the author's research promotion work on evidence in tax law. The author establishes in his work the objective of examining the legal assumption – the presumption, replacing the evidence in the dispute, which, in turn, is the basis for transferring the burden of proof to the other party involved in the dispute. The author comes to the conclusion that the burden of proof, whether transferable or not, has been transferred to the opposing party in cases where the evidence has been replaced by a presumption. The author uses scientific methods in his work: analytical, inductive (cognition), monographic or descriptive, quantitative, qualitative method. The author examines the grounds of proof and the interaction of legal presumption only in the field of public law, in particular in criminal procedural and administrative infringement proceedings. In this work, as in previous works, the author examines procedural issues of administrative offences identical to criminal law, based on the notion that administrative violation rights are viewable like criminal matters, on the same principles and standards of evidence.